SIKAP SUAMI TERHADAP NUSHUZ DALAM AL-QUR’AN (Studi Analisis QS. al-Nisa’ 34 Perspektif Al-Qurtubi Dalam Tafsir Al-Jami’ Li Ahkam Al-Qur’an) - Rozi, Fauzi Fathur; Putri, Yulia Sari (El-Waroqoh : Jurnal Ushuluddin dan Filsafat, 2025)
Being in pairs is one of the natural life that Allah SWT has determined for His people. One of social problems is the high and increasing divorce rate every year. One of empirical facts is existence of disobedience a wife in front of her husband not carrying out the obligations of a wife to her husband with what Allah SWT has commanded. The obligation of husband to treat wife well is an effort to form Sakinah Mawaddah Warahmah household. The purpose of this research is to determine the interpretation of nushuz in QS. al-Nisa '34 Perspective al-Qurtubi in Tafsir Al-Jami' Li Ahkam Al-Qur'an, and to obtain knowledge of the husband's attitude towards nushuz in QS. al-Nisa '34 according al-Qurtubi in Tafsir Al-Jami' Li Ahkam Al-Qur'an. The research method uses library research. The data analysis techniques used content analysis and analytical descriptive. After conducting research, Imam al-Qurtubi interpreted the word nushuz to mean the wife's disobedience and arrogance. Imam al-Qurtubi took the word nushuz from the word al-Nashaz which means something high on the surface of the earth. As for QS. al-Nisa' 34 according to al-Qurtubi there are 3 steps that a husband can take regarding nushuz. The first to advise wife on what Allah SWT has required in the form of good relationships with her husband. Second, turning away from the bed, Imam al-Qurtubi believes that this is a good action, because it has an impact on wife's feelings. Third, hit. He explained that is an educational blow, not a blow that causes pain.